Legitimacy and the European Union : the contested polity - Banchoff, Thomas F., 1964-; Smith, Mitchell P., 1960- (Political dynamics of the EU series., 1999)
Beetham and Lord provide concise and analytical coverage of a key topic within the European Union, that is, the legitimacy of European supra-national governance.